Das Karstphänomen in den verschiedenen Klimazonen. 1.Bericht von der Arbeitstagung der Internationalen Karstkommission: 1.Bericht von der Arbeitstagung der Internationalen Karstkommission - Lehmann, Herbert; Roglič, Josip; Rathjens, Carl; Lasserre, Guy; Harrassowitz, Hermann; Corbel, Jean; Birot, Pierre (ERDKUNDE, 1954)
During the last days of December 1953 the first meeting of the committee on Karst phenomena took place in Frankfort-on-the-Main, presided by the chairman Prof. Dr. Herbert Lehmann. Besides the regular members of the committee some other Karst experts from Yugoslavia, France and Germany joined this meeting. The main topic of the meeting was the question of the development of the Karst phenomena in different climatic zones. In his report Prof. Roglic, Zagreb, dealt with the interior plains or flat floored valleys (Poljes) caused by Karst corrosion. According to Roglic, the development of such interior Karst-plains, surrounded by higher mountains, is caused by the balance of surface water supply and subterranean drainage. They are restricted neither to special levels nor to the hypothetic groundwater levels as Krebs supposed. Bioclimatic factors especially work on the very borders of the plains. In Roglic's opinion the Karst-plaindevelopment originates In the warmer climate of the Pliocene period. Prof. H. v. Wissmann, Tübingen, Prof. H. Lehmann, Frankfurt, and Prof. Lassere, Bordeaux, dealt with the development of Karst in the tropics and within the humid summer-monsoon regions. The tropical Karst (Kegelkarst) displays common trends in spite of its various kinds of development due to its age and rocks: the preparation of many Karst-cones within a limited district,the forming of Karst-border-plains within the level of the Vorfluter. Precipitating with vertical walls (Turm-Karst according to v. Wissmann or Mogotes in Cuiba) are worked out where cones are undercut at their borders by Karst corrosion. Very often you will still recognize the surface arrangement of a regular water system within a set of hollows (as Lehmann and Lassere stated). As well in Guadalupe as in Java there are rounded hills between the Karst-valleys called mornes by Lassere. Regarding the development of Karst arranged in regular lines (gerichteter Karst), there arc, however, at work to a large extent faults and fissures within the limestone. (Lehmann). The activity of Karst corrosion is very intensive in all tropical Karst areas. During the discussion the lade of chemical researches on the Karst phenomena became evident. As pertaining to this matter, Prof. Harrassowitz, Giessen, reported about his researches on the chemistry of rain-water. In general the pH-ration of rain-water is under 7, it can drop down to 3. It is supposed that besides the CO2 production of the tropical vegetation and microorganisms saltpetre acid plays a great role with the intensive Karst corrosion within the tropics. The third day, Prof. /. Corbel, Caluire, reported on Karst within the cold climatic areas (high mountains and polar zones). Within the nival areas where a great amount of melting snow is available at certain times, the development of large subterranean hollows is favoured. Within the areas of permanent frost of the high mountains there are according to Corbel no dolines, and the subterranean Karst phenomena receded. But the development of areas covered by karren (champs de lapiaz) will take place. Within the polar latitudes the karren are generally being distroyed by the influences of frost and snow. Surface solution, however, does not lack totally. Therefore you will find dolines on Spitzbergen. C. Rathjens, Munich, gave a report on his field-studies in the Alps and in Yugoslavia. As to this report the optimum rate of karren development lies between 1700 and 2300 meters of altitude. Above that altitude, within the Frostschuttzone, the karren are destroyed by frost. Prof. Birot, Paris, finally tried to give a climaticmorphological classification of the Karst phenomena based on theoretical considerations. The last day, the committee discussed the problem of how to find an uniform international nomenclature of the Karst phenomena. Even the attempt of finding a comprehensive terminology for the Karst phenomena revealed the difficulties of such an undertaking.